Electrophilic trifluoromethylation of carbonyl compounds and their nitrogen derivatives under copper catalysis. Issue 5 (16th November 2015) - Prieto, Alexis; Baudoin, Olivier; Bouyssi, Didier; Monteiro, Nuno
Abstract : Recent advances in copper-catalyzed electrophilic trifluoromethylation of carbonyl compounds and their nitrogen derivatives are highlighted with particular focus on C–CF3 bond forming reactions. Abstract : Recent advances in electrophilic trifluoromethylation reactions of carbonyl compounds and their usual surrogates are highlighted with particular focus on copper-catalysed (or mediated) C–CF3 bond forming reactions. Ketones and aldehydes (notably via their enol ether and enamine derivatives) enable electrophilic trifluoromethylation at the α-carbon of the carbonyl compounds, whereas aldehyde N, N -disubstituted hydrazones undergo electrophilic attack of the cationic or radical CF3 species at the azomethine carbon, thus providing an umpolung alternative to nucleophilic trifluoromethylation of carbonyl compounds. A reversal in reactivity is also observed for conjugated systems. While α, β-unsaturated ketones regioselectively incorporate the CF3 moiety at the α-position of the enones, trifluoromethylation occurs preferentially at the olefinic β-carbon of the corresponding hydrazones.